Curriculum Development Model as Solution for Adaptive Education in the Era of Disruption - Nur Rofiq (Magister Programme Of Islamic Education Departement at Institut Agama Islam Tarbiyatut Tholabah, 2025)
This study aims to analyze the adaptive curriculum development model as an educational solution in the era of disruption, which is characterized by rapid changes due to technological advances and globalization. The method used is qualitative research with a literature study approach. Data are collected from primary and secondary literature relevant to curriculum development and modern educational challenges. The results show that adaptive curricula should strategically integrate technology while maintaining local cultural values, as well as focus on developing 21st-century skills, such as critical thinking, creativity, and collaboration. The research also highlights the importance of a data-driven approach in curriculum design to ensure local relevance and global readiness. The implications of this study include practical guidance for educational institutions in designing responsive and flexible curricula. However, the limitations of literature review indicate the need for field research to evaluate the effectiveness of adaptive curricula in various contexts. The conclusion of this study reinforces the importance of balancing technological innovation and cultural preservation in education to form a generation that is ready to face global challenges.